Consecutive cyclic esotropia – A case report - Niranjan K Pehere; Usha B Kommineni; Ramesh Kekunnaya (Indian Journal of Ophthalmology, 2019)
Cyclic esotropia, a rare condition of obscure etiology characterized by regularly alternating periods of esotropia and orthophoria. We present a case of a 7-year-old boy who underwent surgical correction for intermittent exotropia elsewhere and developed esotropia with cyclic pattern post-operatively. Initially the cycle was of half-day orthophoria and half-day esotropia, which later became one full day of esotropia and one day of orthophoria. During re-surgery, right lateral rectus was found to have a stretched scar which was resected and then advanced and medial rectus was recessed. Post-surgery the child was orthophoric without cyclic pattern.